2019
DOI: 10.1088/1757-899x/540/1/012002
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Organic Plating Additives Concentration on Carbon Content and Donor Density of Electroplated Tin

Abstract: Pure tin is widely used as a replacement of Pb-Sn eutectic alloy as finish and solder material. This study aims to determine how the increasing concentration of organic plating additives affects the carbon content and donor density of electroplated Sn. Pure tin was electroplated on an Al sheet in a Hull cell using a commercial plating solution. Plating was performed in electrolyte baths with primary additive concentration from 100 mL/L to 600 mL/L, and with secondary additive concentration from 8 mL/L to 48 mL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Fabro et al [39] found that additive content can affect the carbon content in tin-plated coatings. Herein, 2-Butyne-1,4-diol was added to the electrolyte as a carburizer (0, 5, and 10 g/L) to further show that C significantly affects the internal stress of the coating.…”
Section: The Presence Form Of Carbon Elementsmentioning
confidence: 99%
“…Fabro et al [39] found that additive content can affect the carbon content in tin-plated coatings. Herein, 2-Butyne-1,4-diol was added to the electrolyte as a carburizer (0, 5, and 10 g/L) to further show that C significantly affects the internal stress of the coating.…”
Section: The Presence Form Of Carbon Elementsmentioning
confidence: 99%